AHP Approach For Indonesian Public Bus Station Commercial Asset Management Training - Riyardi, Agung; Achyani, Fatchan; Rosy Rochmatullah, Mahameru; Nurul Khassanah, Marsheila; Indriawati, Shofiah (Universitas Muhammadiyah Surakarta, 2025)
Following the government's commitment in the state asset utilization, Indonesian bus stations management develops their commercial assets as a public activity center and a non-tax contributor. The problem is the bus station commercial asset management knowledge and skill should be improved through a specific training. The analytical Hierarchy Process (AHP) approach for the bus station commercial asset management training is essential. The training improves bus station commercial asset management knowledge ans skills by hierarchical expertise and suitable selection. Conducted in the Tirtonadi bus Station located in Indonesian Surakarta city, three stages run the AHP training: Bus station commercial asset management hierarchical expertise and proper selection development, AHP software simulation, and AHP-based test. To create training attractiveness, two treatments are imposed: Asset utilization combination and group division. The training successfully improves bus station commercial asset management knowledge and skill on the hierarchical expertise and suitable selection. In addition, the training raises the bus station management's intention to analyze in general the bus station commercial asset management, readiness to organize the bus station commercial asset management training based on the AHP method, and readiness to become the bus station research key respondent based on the AHP method.